Torngat Mountains Caribou Herd: Inuit Knowledge, culture and values study - Furgal, Chris; Sheldon, Tom (Polar Data Catalogue, 2015)
The Torngat Mountains Caribou Herd (TMCH), inhabiting the northern tip of the Québec-Labrador Peninsula, is not well documented in regard to science or Inuit Knowledge. Limited information on this herd suggests a recent population decrease. Given the importance of caribou for Inuit, precipitous declines in the neighbouring George River Herd, and the upcoming Committee on the Status of Endangered Wildlife in Canada assessment, increasing our understanding of these animals through documentation of IK is critical. This study drew together Inuit from Nunatsiavut and Nunavik and government agencies, from regional to federal levels and across provincial borders. Thirty-three semi-directed interviews were conducted, including participant mapping, with hunters and Elders in Nunavik and Nunatsiavut, representing over seven decades of IK. Thematic content analysis was performed on interview narratives, highlighting IK on this species including new information about topics like the changing role of predators and herd behaviour. Digitized spatial data visualized the long-standing Inuit-caribou relationship in the area, while augmenting the limited existing geographic information.